High‐Performance Biodegradable/Transient Electronics on Biodegradable Polymers. (1st April 2014) - Hwang, Suk‐Won; Song, Jun‐Kyul; Huang, Xian; Cheng, Huanyu; Kang, Seung‐Kyun; Kim, Bong Hoon; Kim, Jae‐Hwan; Yu, Sooyoun; Huang, Yonggang; Rogers, John A.
<x xml:space="preserve">Abstract</x> Materials and fabrication approaches that allow integration of biodegradable/transient electronics onto diverse classes of biodegradable substrates are presented in this article. By first depositing, patterning, and etching the materials for the electronics and then integrating them on a substrate of interest, it is possible to use nearly any type of biodegradable material for this purpose. Component and system‐level studies of various devices and biodegradable polymers illustrate the capabilities and operational aspects. Dissolution studies and mechanics modeling results highlight different modes for transient behavior. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>